Sulfatinib, a novel multi-targeted tyrosine kinase inhibitor of FGFR1, CSF1R, and VEGFR1–3, suppresses osteosarcoma proliferation and invasion via dual role in tumor cells and tumor microenvironment - Liao, Song; Li, Jianxiong; Gao, Song; Han, Yuchen; Han, Xinli; Wu, Yanan; Bi, Jingyou; Xu, Meng; Bi, Wenzhi (Frontiers in Oncology, 2023)
Tumor progression is driven by intrinsic malignant behaviors caused by gene mutation or epigenetic modulation, as well as crosstalk with the components in tumor microenvironment (TME). Considering the current understanding of tumor microenvironment, targeting the immunomodulatory stromal cells such as cancer-associated fibrobalsts (CAFs) and tumor-associated macrophages (TAMs) could provide a potential therapeutic strategy. Here, we investigated the effect of sulfatinib, a multi-targeted tyrosine kinase inhibitor (TKI) of FGFR1, CSF1R, and VEGFR1-3 on the treatment of osteosarcoma (OS). In addition to the well-known effects of VEGFR inhibitor in anti-angiogenesis, other multiple mechanisms were revealed. Sulfatinib suppressed OS cell migration and invasion by inhibition epithelial-mesenchymal transition (EMT) by blocking secretion of bFGF in an autocrine manner. In addition, it regulated immune TME via inhibition of the migration of skeletal stem cells (SSCs) to TME and the differentiation from SSCs to CAFs. Moreover, sulfatinib can suppress OS by modulation of TME via inhibiting M2 polarization of macrophages. Systemic treatment of sulfatinib can reduce immunosuppression cells M2-TAMs, Tregs, and MDSCs and increase cytotoxic T cells infiltration in tumor, lung and spleen. Therefore, our preclinical experiments have shown that sulfatinib can inhibit the proliferation, migration, and invasion of OS by playing dual role on tumor cells and tumor microenvironment simultaneously, and systematically reverse immunosuppression to immune activation status, which could be translated into clinical trials.